Evaluación de alternativas para el sistema de redes sanitarias para el sector Xavier Marcos, cantón Naranjito - Tenemaza Quise, Maycol Raúl (2025)
The objective of this degree project was to design a sanitary sewer system for the Xavier Marcos sector in Naranjito, using information obtained through a topographic survey, as well as hydraulic calculations using the Manning and Hazen-Williams methods. The first part of the work was carried out thanks to the topographic survey of the study area, processing the data in AutoCAD to create the network plan. Subsequently, flow rate and pipe dimension calculations were performed using both methods, evaluating the differences in their results, and selecting the most appropriate design. Finally, a reference budget was prepared based on the results of the selected method. The results of this degree project demonstrate the technical feasibility of the proposed design, constituting a viable solution for the sanitation of the sector.